Boston Celtics - Goodman, Michael E. (Mankato, Minn. : Creative Education, 1993)
A team history of the Boston Celtics, who have continued a tradition of winning in the National Basketball Association.
Keywords: Boston Celtics (Basketball team) -- History -- Juvenile literature; Boston Celtics (Basketball team) -- History; Basketball -- History